Enhancing Educational Equity through Social Psychological Interventions: A Narrative Review - Widyanti, Eka; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2024)
This narrative review examines the effectiveness of social psychological interventions in advancing equity and belonging in education, with a focus on developing countries. Evidence is synthesized across four domains: Social Emotional Learning (SEL), AI-supported interventions, brief positive psychology practices, and multidimensional programs for marginalized students. A systematic search of major databases (Scopus, PubMed, Web of Science, Google Scholar) yielded 85 empirical studies meeting inclusion criteria. Findings show that SEL enhances emotional regulation, peer relations, and academic outcomes; AI-based tools provide scalable support for anxiety and stress; and brief positive psychology practices foster motivation and classroom cohesion. Multidimensional programs addressing academic, psychosocial, and family needs deliver the greatest impact in disadvantaged settings. However, systemic barriers such as policy gaps, limited teacher training, and socioeconomic disparities constrain scalability. This review contributes by integrating AI with SEL in the context of low-resource settings, offering practical recommendations: strengthen teacher capacity, embed mental health in education policy, and build school–community partnerships. Future research should employ longitudinal and culturally grounded designs to test sustainability.